35 rhums [videorecording (DVD)] - Denis, Claire, 1948-; Denis, Claire, 1948-; Descas, Alex; Diop, Mati, 1982-; Dogué, Nicole; Colin, Grégoire (Cinema Guild, 2010)
Lionel is a middle-aged widower who makes his living driving a train and shares an apartment with his twenty-something daughter Josephine. Lionel and Josephine have a warm and caring relationship. Lionel's on-and-off girlfriend Gabrielle and their footloose friend Noe live in the same building. Together the four have fallen into a casual family relationship. When Josephine and Noe become more than friends, Lionel is on edge.